COVID-19 pandemic and intimate partner violence: experiences and outcomes for shelters’ clients in Croatia - Kovčo-Vukadin Irma (Temida, 2022)
Previous research on intimate partner violence (IPV) shows different approaches to answering the question of whether the pandemic has led to an increase and worsening of IPV. The purpose of this study was to examine the impact of the pandemic on the personal and family functioning of victims of IPV, the impact of lockdown on the incidence of violence, help-seeking, coping mechanisms, mental health indicators, and the relationship between the experience of violence, resilience, and mental health indicators. The research sample consisted of women (N=52) who were clients of women’s shelters in Croatia. The pandemic worsened the financial situation of participants and led to changes in the substance use by participants’ partners. Since the introduction of lockdown, there has been an increase in all forms of violence, ranging from 26% (economic violence) to 46% (psychological violence). Participants were most likely to seek help from social welfare centres and the police and showed relatively high resilience and relatively favourable scores on the depression, anxiety, and stress scales.